Response to Selection for Increased Heat Tolerance in a Small Fish Species, With the Response Decreased by a Population Bottleneck - Klerks, Paul L.; Athrey, Giridhar N.; Leberg, Paul L. (Frontiers in Ecology and Evolution, 2019)
Many natural populations are likely to be impacted by increasing temperatures resulting from climate change. The selection pressures exerted by these impacts may allow some populations to adapt to the elevated temperatures – which could reduce climate change’s impact. At present, there is limited evidence for such “evolutionary rescue”. Moreover, the potential for adaptation may be reduced if populations have experienced population bottlenecks as an initial consequence of climate change or due to other human impacts. This study looked at the response to selection in laboratory populations subjected to selection for heat tolerance, in both normal and bottlenecked laboratory populations of the least killifish Heterandria formosa. The bottlenecked populations had undergone a single bottleneck and were found to have fewer microsatellite alleles and reduced genetic diversity. After four generations of selection, heat tolerance had increased – albeit by only 0.1 °C. The increased heat tolerance was more pronounced for normal populations than it was for those that had undergone a population bottleneck. These results show that some populations, under specific conditions, may be able to adapt to elevated water temperatures. However, this response may be too slow for species with a long generation time and further limited in populations that have undergone drastic reductions in population size. In addition, the observed potential for adaptation to physiological heat stress does not equate to evolutionary rescue from other stresses associated with climate change.